Cellular and molecular biology of filamentous fungi - Borkovich, Katherine A.; Ebbole, Daniel J. (Washington, DC : ASM Press, 2010)
Incorporating the latest findings from such disciplines as physiology, taxonomy, genomics, molecular biology and cell biology, this publication is an ideal starting point for any research study of filamentous fungi. Its extensive use of illustrations and tables also makes it an excellent textbook for both graduate and undergraduate students, helping them easily grasp and apply new concepts
1. Introduction to the filamentous fungi -- 2. Replication and expression of the genetic code -- 3. Organelles -- 4. Hyphal growth -- 5. Metabolism -- 6. Photobiology and circadian rhythms -- 7. Nutrient. pH, and stress sensing -- 8. Sexual development -- 9. Asexual sporulation -- 10. Interactions of fungi with plants or other fungi -- 11. Animal pathogens
Includes bibliographical references and index
Keywords: Filamentous fungi; Fungal molecular biology; Fungi -- metabolism; Fungi -- Genetics; Microbiological Phenomena